2022
DOI: 10.1111/ggi.14389
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of severe sarcopenia in Japanese patients with acute heart failure

Abstract: AimSarcopenia is a geriatric condition characterized by progressive loss of skeletal muscle mass and function. The definition and diagnosis of sarcopenia is inconsistent between different populations and is still evolving. Herein, we investigated the prevalence and clinical implications of severe sarcopenia using the Asian Working Group for Sarcopenia (AWGS) 2019 criteria in Japanese patients with acute heart failure (HF).MethodsOverall, 272 patients admitted for acute HF were evaluated for sarcopenia using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…When compared to patients hospitalized with acute HF, both the percentages of overall sarcopenia and severe sarcopenia were lower in our study [25]. This finding can be easily explained by the acute care (hospital) setting strong influence on the development of sarcopenia (acute disease, immobilization, food restrictions, etc.…”
Section: Discussionmentioning
confidence: 52%
“…When compared to patients hospitalized with acute HF, both the percentages of overall sarcopenia and severe sarcopenia were lower in our study [25]. This finding can be easily explained by the acute care (hospital) setting strong influence on the development of sarcopenia (acute disease, immobilization, food restrictions, etc.…”
Section: Discussionmentioning
confidence: 52%
“…In a clinical study of 272 hospitalized patients with acute heart failure, sarcopenia diagnosed using BIA was related to cardiac death or heart failure rehospitalization. 25 Moreover, we have already reported from FRAGILE‐HF that sarcopenia assessed using BIA was independently associated with 1 year mortality, irrespective of left ventricular ejection fraction. 7 However, no study has reported an association between sarcopenia defined using DEXA and prognosis, although DEXA may be superior to BIA in terms of its prognostic value in patients with heart failure.…”
Section: Discussionmentioning
confidence: 95%
“…The prognostic impact of sarcopenia has been reported in patients with heart failure, and previous studies have evaluated sarcopenia using BIA. In a clinical study of 272 hospitalized patients with acute heart failure, sarcopenia diagnosed using BIA was related to cardiac death or heart failure rehospitalization 25 . Moreover, we have already reported from FRAGILE‐HF that sarcopenia assessed using BIA was independently associated with 1 year mortality, irrespective of left ventricular ejection fraction 7 .…”
Section: Discussionmentioning
confidence: 96%
“…1, 229 patients hospitalized with acutely DHF were assessed for eligibility. Thirty-two patients were not included in the study due to in-hospital deaths (10), inability to participate (19), or refusal (3). Thus, 191 patients were nally enrolled, of whom 7 were lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with HF and sarcopenia are more prone to develop physical frailty and related negative health outcomes, with a higher risk of HF progression with the need for hospitalization [5] and an increased mortality rate [8,9]. Notwithstanding, very few studies have attempted to evaluate the shortterm prognostic signi cance of sarcopenia in older individuals with HF [10][11][12][13]. According to the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) guidelines [6], all patients with suspected sarcopenia should undergo the SARC-F, a 5-item questionnaire that is self-reported by patients based on their perception of limitations in strength, walking ability, rising from a chair, stair climbing, and experiences with falls.…”
Section: Introductionmentioning
confidence: 99%